Analisis Kesulitan Menyelesaikan Soal Open Ended Pada Materi Bilangan Kelas Vii Semester Gasal Smp Negeri 3 Sawit Tahun Pelajaran 2016/2017 - Ratnasari Setyaningrum, Nofi; , Rita P. Khotimah.S.Si., M.Sc (2017)
This research aims to describe the difficulty and analyze the causal factors of students' difficulty in solving the open ended questions of numeric material. Type of this research is descriptive qualitative. The technique of data collection uses test, interview, and documentation. The data validity uses the triangulation technique. The data analysis is through the stage of data reduction, data display, and drawing conclusion. The results of this research showed that the kinds of difficulty faced by the students are: 1) difficulty in understanding questions (44,44%) that is the students did not understand the question given in open ended type; 2) difficulty in transforming question (55,55%) that is the students were not able to determine the mark of arithmetic operation to mean 'the temperature increase' when doing the numeric material question; 3) difficulty in the process skill (61,11%) that is the students could not do the arithmetic operation; 4) difficulty in drawing conclusion (83,33%) according to the answer in the process of solving the queation. The causal factors of difficulty in solving the open ended question covers: 1) thee students were not used to face open ended question; 2) the students' less understanding on the numeric material; 3) the students' inappropriate habit of learning; 4) the students' habit of seeing their friends' answer when doing the question; 5) less carefulness; and 6) did not recheck the answer. Keywords: difficulty factor kesulitan, kind of difficulty, difficulty of solving the question, open ended question.